Government and community efforts in upgrading infrastructure in informal areas- the case of Izbit ElHaggana - Wahby, Noura Medhat (AUC Knowledge Fountain, 2013)
Realizing the magnitude of informality as a façon-de-vie in Cairo as in other megacities, this research focuses on the urban poor in their attempts to provide a decent standard of living using their own efforts, within the context of the lack of government engagement and limited resources. The purpose was to answer the research question how community organizations and state actors interact in providing key infrastructure in informal areas, taking Izbit ElHaggana as an area of study. The objective was to determine the processes of how community self-help schemes and government efforts to install and upgrade infrastructure in informal areas operate and are maintained. This thus allowed us to recognize quality and sustainability issues, as well as potential for integrated/inclusive upgrading policies; and whether the government can afford to reject informal infrastructure. Qualitative interviews were conducted with community members, government officials and experts on informality to provide holistic perceptions on the upgrading paradigm. The study findings provided an insight to two case studies of self-help water installations in the two districts of ElHaggana, as well as an insight into electricity and sewerage connections, regarding gehood zateya processes- incremental networking, innovation strategies, communal networks and self-sufficiency, sub-optimal quality, and sustainability. The findings also shed light on the themes of informal social structures and interaction with formal systems. The research indicates that local self-help initiatives often override non-functioning formal systems, while local governments stubbornly avoid collaboration as back participation in initiatives. In addition, community interviews presented citizens caught in a trap between the need to regularize and mistrust of formalization given the unstable official recognition.